2021
DOI: 10.1108/jpbm-09-2020-3071
|View full text |Cite
|
Sign up to set email alerts
|

Constructing generational identity through counterfeit luxury consumption

Abstract: Purpose This paper aims to theorize counterfeit luxury consumption among millennials from a generational identity perspective. Design/methodology/approach The paper proposes and tests a model of counterfeit buying behavior using an online survey of 467 millennial respondents. The study uses multi-item measures from the extant literature and uses the structural equation modeling technique to test the proposed hypotheses. Findings The findings reveal when millennials have a self-defining relationship with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 164 publications
(413 reference statements)
3
27
0
Order By: Relevance
“…Previous research employed market mavens with other consumer-related constructs (Chelminski & Coulter, 2007;Cleveland & Bartikowski, 2018;Reinecke Flynn & Goldsmith, 2017), revealing its antecedents (Flynn, Goldsmith, & Pollitte, 2016;Gauri, Harmon-Kizer, & Talukdar, 2016;Zhang & Lee, 2014) and its significant and positive effect on different consumer behaviour outcomes (Gauri et al, 2016;Hanson, Kukar-Kinney, & Yuan, 2021;Rubio, Villaseñor, & Oubiña, 2015). In terms of generational differences, maven has recently attracted attention and has been subject to a limited number of studies revealing the general attitudes of a certain generation group (Hourigan & Bougoure, 2012;Khan, Fazili, & Bashir, 2022) or comparison between generations (Brosdahl & Carpenter, 2011;Goldring & Azab, 2021).…”
Section: Market Mavensmentioning
confidence: 99%
“…Previous research employed market mavens with other consumer-related constructs (Chelminski & Coulter, 2007;Cleveland & Bartikowski, 2018;Reinecke Flynn & Goldsmith, 2017), revealing its antecedents (Flynn, Goldsmith, & Pollitte, 2016;Gauri, Harmon-Kizer, & Talukdar, 2016;Zhang & Lee, 2014) and its significant and positive effect on different consumer behaviour outcomes (Gauri et al, 2016;Hanson, Kukar-Kinney, & Yuan, 2021;Rubio, Villaseñor, & Oubiña, 2015). In terms of generational differences, maven has recently attracted attention and has been subject to a limited number of studies revealing the general attitudes of a certain generation group (Hourigan & Bougoure, 2012;Khan, Fazili, & Bashir, 2022) or comparison between generations (Brosdahl & Carpenter, 2011;Goldring & Azab, 2021).…”
Section: Market Mavensmentioning
confidence: 99%
“…The study of Chao and Yu (2021) indicated that playing online games have negative impact on self-consciousness of adolescents. The study performed by Khan et al (2022) about generational identity construction by fake luxury consumption showed that public selfconsciousness provided contribution to generational identities of y-generation. Kuhn (2022) also made studies on online meeting media like Zoom, which were more commonly used due to Covid 19 pandemic conditions, in which a person could see himself/ herself on the screen.…”
Section: Perceived Inconsistency Between An Attitude … and A Behaviormentioning
confidence: 99%
“…According to generational cohort theory, a generational cohort has distinctive characteristics and their integration forms a generational identity which can be considered as a social identity based on the fact that it is socially constructed (Joshi et al, 2010;Lyons et al, 2019). Generational identity is characterized by shared values (Khan et al, 2021;Lyons & Schweitzer, 2017). The degree to which individuals identify with a specific social group shows how likely they are to endorse the customs and values of that social group (Porck et al, 2019).…”
Section: Generational Identity Of Millennialsmentioning
confidence: 99%
“…According to Twenge and Campbell (2008), generational differences arise from either psychological or technological differences. Generational identity of Millennials, which is derived from generational cohort theory and social identity theory, is associated with the shared values of Millennials (Joshi et al, 2010;Khan et al, 2021;Lyons et al, 2019;Lyons & Schweitzer, 2017;Porck et al, 2019). Millennials have been widely characterized as an entitled generation with unique work values (Allen et al, 2015;Credo et al, 2016;Harvey & Dasborough, 2015;Hui et al, 2020;Murphy, 2012;Naim & Lenka, 2018;Njoroge et al, 2021;Pasko et al, 2020;Schullery, 2013;Twenge & Campbell, 2008;Twenge, 2013).…”
Section: Knowledge Gaps In Literature and Future Research Directionsmentioning
confidence: 99%